New teaching strategies in dentistry: an experience in a Brazilian dental school - Miranda, Keila Cristina; Abreu, Marcela Freitas Fernandes de; Bardini, Vivian Silveira dos Santos; Tango, Rubens Nisie; Vasconcellos, Luana Marotta Reis; Salgado, Miguel Angel Castillo; Spalding, Marianne (Revista da ABENO, 2022)
The need for new teaching-learning strategies stems from the great change society is going through. The so-called digital natives are part of a generation that lives in a hyperactive rhythm making it increasingly difficult to adapt to traditional classrooms. In Dentistry Courses, new strategies and pedagogical tools have been used, such as active learning methodologies. In this context, the Discipline of Histology of the Dentistry Course has been proposing the use of some innovative pedagogical strategies. This work will present the experience with team-based learning (TBL), which articulates individual (iRAT) and group activities (gRAT), stimulates the application of concepts and can articulate with other methodologies such as flipped classroom, case study and problematization. This study also analysed students’ performance in iRAT and gRAT with the application of TBL and discussed the results achieved. It was conducted by analysing the scores of 240 first-year students of the Histology course in 2016, 2017 and 2018. Student scores, individually and in groups, were statistically analysed by the paired student t-test. Comparisons were made between the iRAT and gRAT activities about gender and the full-time and night classes by the one-way ANOVA and Kruskal-Wallis test. All students obtained higher group scores when compared to individual test results (p <0.001). There was no significant difference between sexes and study period. Group performance exceeds individual performance. From this, it can be inferred that TBL can be a good strategy to use in dentistry, as an interaction between students leads to higher performance and problem-solving capacity.